Innovative investment type of economics as a condition for its effective functioning - Bondarenko, Yu. H.; Bahrii, Z. R. (Видавництво Львівської політехніки, 2014)
The necessity of the national economy transition to the innovative way of development is substantiated. The main characteristics of such a transition are presented. The experience of foreign countries and the advantages from introduction of innovations at an enterprise are generalized. The interrelation and interaction of investments and innovations are determined. The importance and place of investments in the innovative-type state are proven. Обґрунтовано необхідність переходу національної економіки на інноваційний шлях розвитку, наведено його основні характеристики, узагальнено досвід іноземних держав та переваги упровадження інновацій на підприємстві. Визначено взаємозв’язок і взаємодію інвестицій та інновацій. Доведено вагомість і місце інвестицій у інноваційному типу розвитку держави.
Інноваційно-інвестиційний тип розвитку економіки як умова її ефективного функціонування
Keywords: innovative type of development; innovative economy; innovative activity; investments; investment activity; competitive activity; інноваційний тип розвитку; інноваційна економіка; інноваційна діяльність; інвестиції; інвестиційна діяльність; конкурентна боротьба